Novel bisthioether derivatives containing a 1, 3, 4‐oxadiazole moiety: design, synthesis, antibacterial and nematocidal activities. Issue 4 (20th December 2017) - Li, Pei; Tian, Pingyi; Chen, Yongzhong; Song, Xianpeng; Xue, Wei; Jin, Linhong; Hu, Deyu; Yang, Song; Song, Baoan
Abstract: BACKGROUND: The literature shows that bisthioether and 1, 3, 4‐oxadiazole derivatives exhibit a wide variety of biological activities. In this study, a series of novel bisthioether derivatives containing a 1, 3, 4‐oxadiazole moiety were synthesized and their antibacterial and nematocidal activities investigated. RESULTS: Among the title compounds evaluated, compound4f demonstrated the best antibacterial activities against rice bacterial leaf blight, rice bacterial leaf streak and citrus canker caused by Xanthomonas oryzae pv. oryzae ( Xoo ), Xanthomonas oryzae pv . oryzicola ( Xoc ) and Xanthomonas axonopodis pv. citri ( Xac ), with EC50 values of 4.82, 11.15 and 16.57 µg mL –1, respectively, which were even better than those of thiodiazole copper and bismerthiazol. Meanwhile, compound4f had better in vitro nematocidal activity against Caenorhabditis elegans at 48 h, with an LC50 value of 2.89 µg mL –1, which was superior to those of ethoprophos and fosthiazate. In addition, greenhouse trials indicated that compound4f was effective in reducing rice bacterial leaf blight relative to thiodiazole copper and bismerthiazol. CONCLUSION: A series of novel bisthioether derivatives containing a 1, 3, 4‐oxadiazole moiety were synthesized and bioassay results showed that compound4f exhibited the best antibacterial and nematocidal activities. © 2017 Society of Chemical Industry Abstract : A series of novel bisthioether derivatives containing 1, 3, 4‐oxadiazole moiety were synthesized and bioassay results showed that compound4f exhibited the best antibacterial and nematocidal activities.